DESCRIPTION OF MATHEMATICS REASONING ABILITY IN SOLVING STORY QUESTIONS BASED ON COGNITIVE STYLES AND INITIAL ABILITY OF STUDENTS - Mutmainnah Mutmainnah; Usman Mulbar; Djadir Djadir (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
This study is descriptive research which employs qualitative approach, aims at describingMathematics reasoning ability in solving story questions based on cognitive style and initial ability of students. The cognitive styles examined are Field Independent (FI) and Field Dependent(FD). Where as, initial ability of students arecategorized as high and low. The research site was at MtsN 1 Makassar City with 8 students of grade VIII as the research subjects. The research subjects represented four categories, namely (1) FI with high initial ability, (2) FI with low initial ability, (3) FD with high initial ability and (4) FD with low initial ability. Data collection techniques were conducted through interview based on mathematics reasoning ability test. The research instruments were Group Embedded Figure Test (GEFT), initial ability test, mathematics reasoning ability test, and interview guidance which were valid and reliable. The results of the study reveal that: (1) FI subjects with high initial ability has a good reasoning level in understanding the structure in solving mathematics problems, (2) FD subjects with high initial ability has minor problems in understanding the structure when solving rectangular story questions but still able to arise his reasoning ability, (3 ) FI subjects with low initial ability has reasoning ability but inaccurate in conducting solution plan, and (4) FD subjects with low initial ability has less  reasoning ability so that they need guidance in solving rectangular story questions